Examining the State of Pastoral Resources under Common Property Regime, and Pastoralists Accessibility in Drylands of Niger and Nigeria - Abdullahi Umar; Muhammmad Nuraddeen Danjuma (MO.RI Publishing, 2022)
Pastoralism faces changes in Nigeria and Niger. This raised the call for interrogating the two countries’ stewardship of pastoral resources. The objectives of this study were to examine state of pastoral resources and make comparison on how legal and institutional, frameworks determine access to these resources in the drylands of Niger and Nigeria. Cropland, land under permanent meadows and pasture and forests lands data for Niger and Nigeria for 1995, 2000, 2005, 2010, 2015 and 2020 were downloaded from UN Food and Agricultural Organisation website. Seven communities namely: Abalak, Dakoro and Gaya (in Niger) and Augei, Dakingari, Gummi and Wurno (in Nigeria) were purposively selected and pastoralists were interviewed and/or observed. Descriptive statistics was employed in data analysis. We found that croplands in the two countries have significantly expanded. These expansions might have benefited from forestland depletion but not from land under permanent meadows and pastures (LUPMP) especially in Niger. LUPMP has increased in area in the two Countries. Pastoralists in Niger abhor privatization of pastoral resources. They also demand more access to pasture. In Nigeria, encroachment of pastoral resources by farmers, private ranches and mining, scarce and decaying infrastructure, lack of tenure right to pastoral resources are some of the problem’s pastoralists face. We conclude that agricultural intensification, through its conversion of other forestlands, threatens livestock production more essentially in Niger than in Nigeria and recommend that pastoral resources need to be prioritized by Governments as a regional strategy for communities’ livelihood enhancement and conflict prevention mechanism.